L. S. Vigotski e o ensino de arte: A educação estética (1926) e as escolas de arte na Rússia 1917-1930 - Wedekin, Luana Maribele; Zanella, Andrea Vieira (UNICAMP - Faculdade de Educação, 2016)
Abstract This article discusses the relationship between The Aesthetic Education (1926) by Lev S. Vigotski and the context of restructuring education and teaching of the arts after the Russian Revolution of October 1917. This bibliographical study creates a dialogue between Vigotski and historians who have researched the art schools before and after the Revolution of 1917. The following issues guide the analysis: Were Vigotski's ideas on aesthetics consistent with established practices in these new institutions? Were these ideas related to policies for teaching art in the period? We concluded that The Aesthetic Education was forged on Vigotski´s practical experience in dialogue with the art and science of his time. The author remained independent of the official thinking, what keeps his work relevant and powerful to think about teaching arts today.

Resumo Problematizam-se, neste artigo, as relações entre A educação estética (1926), de Lev S. Vigotski, e o contexto de reestruturação da educação e do ensino das artes após a Revolução Russa de outubro de 1917. Trata-se de pesquisa bibliográfica que operou um diálogo entre Vigotski e os historiadores que estudaram as escolas de arte anteriores e posteriores à Revolução de 1917. Orientaram as análises as seguintes questões: as ideias de Vigotski sobre estética estavam em consonância com as práticas estabelecidas nessas novas instituições? Como essas ideias se relacionavam com as políticas para o ensino de arte no período? Constatou-se que A educação estética foi forjada na experiência prática de Vigotski em diálogo com a arte e a ciência de sua época, pautada em pensamento independente dos encaminhamentos oficiais, mas cuja qualidade das reflexões e dos princípios garante a atualidade e a potência da obra para pensar o ensino de arte hoje.
L.S. Vygotsky and Teaching Arts: The aesthetic education (1926) and the Art Schools in Russia 1917-1930
Keywords: Vigotski; aesthetic education; teaching arts; Russian art; Vigotski; educação estética; ensino de arte; arte russa